New atropisomers derived from amidinoquinoxaline N-oxides: Synthesis and NMR characterization - Díaz, Jimena Estela (2010)
The complete 1H and 13C NMR characterization of some representative examples of five and six-membered amidinoquinoxaline N-oxides 1 with dissymmetric aryl substituents and their methiodides 2 is reported. Compounds 1 were synthesized by ring closure of N-arylacetyl-N′-(2- nitrophenyl)alkylenediamines 3, followed by spontaneous heterocyclization. Methiodides 2 were prepared by quaternization of the parent heterocycles with methyl iodide. Complete assignment of the 1H and 13C NMR resonances of compounds 1,2 was made on the basis of the correlations observed in their HSQC, HMBC and NOESY spectra. The 1H NMR spectra of compounds 1,2 display diasterotopicity of methylenic hydrogens, indicative of molecular chirality due to the presence of a chiral axis (ONC-Ar bond). Further support for the existence of the atropisomers for compounds 1a,b is presented, on the basis of spectral and theoretical data.